Income support programmes for the older adults in South Asia: a scoping review protocol - Shradha S Parsekar; Eti Rajwar; Bhumika Tumkur Venkatesh; Prachi Pundir; Tobias Vogt (BMJ Open)
Introduction South Asian countries are ageing and experiencing a rapid increase in proportion of the older population. Income support programmes are of central importance for the older adults as they may help to mitigate the poverty risks associated with ageing and losing the ability to generate income from labour. Evidence related to the income support programmes can help in understanding whether the programmes have been impactful. This scoping review will map the evidence (and gaps) related to income support programmes and create a base to identify the feasibility of future primary research and/or the scope of systematic reviews in the areas where evidence is available.Methods and analysis The Joanna Briggs Institute scoping review methodology will be followed. Eligibility criteria for the scoping review will be based on the ‘PCC’ or the ‘Population–Concept–Context’ concept. Advanced search for the relevant articles will be conducted in MEDLINE (via PubMed), Embase, Scopus, Campbell Collaboration, 3ie International Initiative for Impact Evaluation and Web of Science. Additional resources search will be conducted in important organisational websites. Findings of the scoping review will be summarised using descriptive information (frequencies and percentages) for the available evidence on concept (ie, income support programmes), population characteristics and other study variables.Ethics and dissemination The review is based on data from available literature, hence an ethical approval is not necessary. With this review, we attempt to provide recommendations to the research community and the policymakers about the currently available evidence and the research required for income support of older adults in South Asia, so that resources can be directed towards addressing the same. We plan to disseminate the findings through presentation in international conference and publication in a peer-reviewed journal.Review registration Not registered.